Proteome study of cutaneous lupus erythematosus (CLE) and dermatomyositis skin lesions reveals IL-16 is differentially upregulated in CLE - Timothy B. Niewold; Alexander Meves; Julia S. Lehman; Karin Popovic-Silwerfeldt; Aliisa Häyry; Therese Söderlund-Matell; Cristine M. Charlesworth; Benjamin Madden; Ingrid E. Lundberg; Marie Wahren-Herlenius; Elisabet Svenungsson; Vilija Oke (Arthritis Research & Therapy, 2021)
Abstract Background The objective of the study was to explore the disease pathways activated in the inflammatory foci of skin lesions in cutaneous lupus erythematosus (CLE) and dermatomyositis (DM). Methods Skin biopsies acquired from active CLE and DM lesions, patient (PC), and also healthy controls (HC) were investigated. Biopsy sections were examined by a pathologist, inflammatory foci were laser micro-dissected and captured, and proteins within captured tissue were detected in an unbiased manner by mass spectrometry. Protein pathway analysis was performed by the string-db.org platform. Findings of interest were confirmed by immunohistochemistry (IHC). Results Proteome investigation identified abundant expression of interferon-regulated proteins (IRP) as a common feature of CLE and DM. Interleukin (IL)-16 was the only abundant cytokine differentially expressed in CLE compared to DM. Caspase-3, an enzyme that cleaves IL-16 into its active form, was detected in low levels. Significantly higher proportion of IL-16- and caspase-3-positive cells was identified in CLE lesions in comparison with DM, PC, and HC. Proteomic results indicate more abundant complement deposition in CLE skin lesions. Conclusions Using unbiased mass spectrometry investigation of CLE and DM inflammatory infiltrates, we confirmed that high IRP expression is a common feature of both CLE and DM, while IL-16 is the only differentially expressed cytokine in CLE. IHC confirmed high expression of IL-16 and caspase-3 in CLE. Our novel molecular findings indicate that IL-16 detection could be useful in differential diagnostics between the two conditions that can display similar histopathological appearance. IL-16 could be of interest as a future therapeutic target for CLE.